2018
DOI: 10.1002/mc.22900
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of differential circular RNA expression in a mouse model of colitis‐induced colon carcinoma

Abstract: Circular RNAs (circRNAs) have received increasing attention for their involvement in the pathogenesis of cancer; however, the characterization and function of circRNAs in colitis-induced colon carcinoma remains largely unknown. A colitis-induced colon carcinoma model was established in mice treated with azoxymethane-dextran sodium sulfate (AOM-DSS), and the circRNA profile was screened by next generation sequencing. Bioinformatic tools, including Gene Ontology (GO) analysis, Kyoto Encyclopedia of Genes and Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Zeng et al also detected 431 DECs (192 upregulated and 239 downregulated) in CRC tissues from patients with lung metastasis compared with CRC tissues from patients without metastasis using a high-throughput microarray assay [58]. Interestingly, Yuan et al and Chen et al searched for tumorigenesis-and metastasis-associated circRNAs in CRC mouse models using RNA-seq; finally, mmu-circ-001226/mmu-circ-000287 and circ-NSD2 (mm9_circ_003195) were identified to be associated with CRC tumorigenesis and metastasis, respectively [59,60].…”
Section: Dysregulated Circrnas In Crc Tissuesmentioning
confidence: 99%
“…Zeng et al also detected 431 DECs (192 upregulated and 239 downregulated) in CRC tissues from patients with lung metastasis compared with CRC tissues from patients without metastasis using a high-throughput microarray assay [58]. Interestingly, Yuan et al and Chen et al searched for tumorigenesis-and metastasis-associated circRNAs in CRC mouse models using RNA-seq; finally, mmu-circ-001226/mmu-circ-000287 and circ-NSD2 (mm9_circ_003195) were identified to be associated with CRC tumorigenesis and metastasis, respectively [59,60].…”
Section: Dysregulated Circrnas In Crc Tissuesmentioning
confidence: 99%
“…More recently, there have been a growing number of publications focusing on the roles of circRNAs in the pathogenesis of malignancies, such as hepatocellular carcinoma (HCC) [3], gastric cancer [4], non-small-cell lung cancer (NSCLC) [5] and breast cancer [6]. Particularly, with the development of high-throughput sequencing technology and microarray assay, numerous differentially expressed circRNAs are identified in tumor tissues [7,8], while the underlying molecular mechanisms of circRNAs in the carcinogenesis of malignant tumor need yet to be uncovered.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this study explored the possible connections between circRNAs and miRNAs and attempted to establish a network. It was found that mmu_ circRNA_001226 and mmu_circRNA_000287 were the first two key points in this network 148 . The mmucirc-001226/mmu-circ-000287-miRNA-mRNA network may be the potential mechanism for CAC 148 .…”
Section: Circrnas In Cacmentioning
confidence: 90%
“…Yuan et al 148 reported that altered expression profiles of circRNAs are involved in CAC development. Compared with in normal colonic tissues, mmu_circRNA_001801, mmu_circRNA_002987, and mmu_circRNA_001155 were the most increased circRNAs, and mmu_circRNA_00287, mmu_circRNA_003037, and mmu_circRNA_001226 were the most decreased circRNAs 148 . Moreover, this study explored the possible connections between circRNAs and miRNAs and attempted to establish a network.…”
Section: Circrnas In Cacmentioning
confidence: 99%